Gaming in the cloud: 5G as the pillar for future gaming approaches - Baena, Carlos; Fortes-Rodríguez, Sergio; Peñaherrera-Pulla, Oswaldo Sebastián; Baena-Martínez, Eduardo; Barco-Moreno, Raquel (IEEE, 2024)
One key element in the future of the video game industry is the adoption of the cloud gaming paradigm. This model allows high-quality and on-the-move gaming experiences in terminals with minimal capacity. However, such an approach establishes hugely challenging requirements on the network side to support the high amount of data exchanged with stringent latency demands. In this sense, 5G features are expected to achieve these requirements and become the main enablers for the pervasive adoption of cloud gaming. The present work identifies critical factors in the cloud gaming user's experience and the impact of the network on it. Along these lines, the most important aspects in 5G networks that will support the provision of cloud gaming are explained, offering a performance comparison with other network technologies through experiments in real-world network deployments. The outcome shows the potential of 5G networks in contrast with legacy technologies. From this, the 5G features destined to improve the delivery of the service are discussed, exposing the future challenges to address.
Keywords: Videojuegos; Servidores web; Streaming; Mercado--Análisis; 5G mobile communication; Market opportunities; Market research; Packet loss; Streaming media; Cloud gaming; User experience; Video games; Servers